Chemical vapor deposition merges MoS2 grains into high-quality and centimeter-scale films on Si/SiO2. Issue 10 (18th February 2022) - Singh, Mukesh; Ghosh, Rapti; Chen, Yu-Siang; Yen, Zhi-Long; Hofmann, Mario; Chen, Yang-Fang; Hsieh, Ya-Ping
Abstract : Control of the precursor transport through oxygen dosing yields increased MoS2 coverage and increased connectivity between crystalline MoS2 domains. Abstract : Two-dimensional molybdenum disulfide (MoS2 ) has attracted increasing attention due to its promise for next-generation electronics. To realize MoS2 -based electronics, however, a synthesis method is required that produces a uniform single-layer material and that is compatible with existing semiconductor fabrication techniques. Here, we demonstrate that uniform films of single-layer MoS2 can be directly produced on Si/SiO2 at wafer-scale without the use of catalysts or promoters. Control of the precursor transport through oxygen dosing yielded complete coverage and increased connectivity between crystalline MoS2 domains. Spectroscopic characterization and carrier transport measurements furthermore revealed a reduced density of defects compared to conventional chemical vapor deposition growth that increased the quantum yield over ten-fold. To demonstrate the impact of enhanced scale and optoelectronic performance, centimeter-scale arrays of MoS2 photosensors were produced that demonstrate unprecedentedly high and uniform responsivity. Our approach improves the prospect of MoS2 for future applications.